Pengaruh Kepemilikan Institusional, Komposisi Dewan Komisaris, Kinerja Perusahaan terhadap Luas Pengungkapan Corporate Social Responsibility di dalam Sustainability Report pada Perusahaan Manufaktur yang Terdaftar di BEI - Sari, Ati Retna; Sukoharsono, Eko Ganis; Sutrisno (Universitas Brawijaya, Indonesia, 2013)
Business firm development in Indonesia shows rapid progress. CSR (Corporate Social Responsibility) is an issue that attracts enormous interest, particularly in Indonesia; in addition, Corporate Social Responsibility itself is the responsibility of the company in general. The development causes companies are compelled to disclose their social responsibility report.In Indonesia, how far a company should handle the CSR has become interesting an interesting discussion, as considering that there is a lack of research on the factors that affect the disclosure extent of the corporate social responsibility. The purpose of this study is to examine the effect of corporate governance (institutional ownership and the composition of the board of commissioners) and firm performance (ROE and ROI) as well as the size of the company to the extent of disclosure of Corporate Social Responsibility in the Sustainability Report. The data used are secondary data from published financial statements; in addition, the observed reports are financial statements published in 2000-2011. The sample numbers of the firm in this study are 39 companies. This study uses multiple regression data analysis techniques. The test results reveal that from the observed variables, there are three variables that influence the disclosure extent of the Corporate Social Responsibility in the Sustainability Report. Those three variables include Institutional Ownership, ROE and ROI. There is no significant relationship between board composition and firm size with the extent of Corporate Social Responsibility disclosure in the Sustainability Report.